Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Studies in structural characterization and correlation with the catalytic activity of an efficient and stable WOx/SBA-15 nanocomposite catalyst - Bordoloi, Ankur; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A new WOx/SBA-15 nanocomposite catalyst system was developed by hydrothermal synthesis. The material was characterized by X-ray diffraction, high-resolution transmission electron microscopy, sorption analysis, FT-IR, CP-MAS NMR, XPS, and energy-dispersive X-ray analysis. Various types of aromatic and aliphatic sulfides were selectively oxidized to sulfoxides in good to excellent yields without becoming overoxidized to the sulfones using 70% aq. tert-butyl hydrogen peroxide in the presence of nanocomposite catalyst at room temperature. The catalyst could be easily recovered and reused for at least eight reaction cycles under the reaction conditions described here with no significant loss of reactivity. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: catalytic oxidation; mesoporous materials; Sulfides; Sulfoxides; tungsten oxide nanocluster

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx